Estudos citogenéticos em algumas espécies de peixes da família loricariidae pertencentes à Bacia do Rio Piracicaba - Camilo, Fábio Mendes (Universidade Federal de São Carlos, 2004)
Willing to develop the number cytogenetically reports on fish species belonged to the Loricariidae family, the actual work had as the basic aim to feature chromosomically three specimen of fishes from the basin of the Piracicaba river: Hypostomus albopunctatus; Liposarcus anisitsi and Corumbataia cuestae. The specimen H. albopunctatus and L. anisitsi which were previously feature cytogenetically in other basins and these cytogenetically data are correlated to the data obtained on this work, concerning to the species C. cuestae, the cytogenetically data obtained puts together the first feature of chromosome framing of a specie belonging to this king. The samples were exposed to conventional and differential cytogenetically methodologies, involving bandings-C, Ag- RON e FISH (hybridization fluorescent in situ) with probe 18S. The specimen H. albopunctatus and L. anisitsi were collected in Piracicaba river (Piracicaba country, SP), the H. albopunctatus, showed 2n=74 chromosomes (10M, 20SM, 44ST/A) the parts organized of nucleolus were seen as diversified, with until 3 chromosome marked by Silver Nitrate, featuring on this specie multiple RONs, being acrocentric chromosome with terminal bandings on short arms and of small submetacentric pair with telomeric bandings on short arms, coinciding to the results obtained by de FISH technique. The preparations to marking C, made it clear large heterochromatin interstitial arm of a acrocentric chromosomal pair, on short arm of a submetacentric pair pericentromeric marking of a long arm of a large metacentric pair beyond short markings in centromeric parts of chromosomal submetacentric. The samples of L. anisitsi showed 2n=52 chromosome (16M, 28SM, 6ST, 2A), after Silver Nitrate staining, the markings were placed on terminal position of a long arm by a submetacentric chromosomal pair, featuring a single RON, confirmed by FISH. The cytogenetical result obtained with two specimen on the actual work when compared to the same specimen already described belonged to other basins they show a considered conservation state. Differences were found, however, we might suggest that these specimen seem to be cytogenetically very preserved when we compare the cytogetical results already obtained to the species H. albopunctatus and L. anisitsi available in literature. The specie Corumbataia cuestae, colleted at Lapa river (Itirapina county-SP), showed 2n=54 chromosomes (28M; 20SM; 6ST/A) just to Nucleolus Organized Regions were observed, placed on the terminal part of short arm from number 2 pair featured as metacentric, and they were seen as heteromorphic thought the size, sequential analysis of metaphases in Giemsa/Silver and Giemsa/banding-C, discovered that the secondary constrictions correspond to RONs. The constitutive heterochromatin pattern is observed clearly nucleolus chromosomal pair, with large pericentromeric heterochromatic blocks. The results obtained to offer new subsidy for studies evolution of Loricariídae, to open perspective for best understanding of correlations between species of Hypostominae and Hypoptopomatinae.
Keywords: Citogenética; Bagre (peixe); CIENCIAS BIOLOGICAS::GENETICA